2012
DOI: 10.1094/pdis-03-12-0276-pdn
|View full text |Cite
|
Sign up to set email alerts
|

First Report of a Fusarium sp. and Its Vector Tea Shot Hole Borer (Euwallacea fornicatus) Causing Fusarium Dieback on Avocado in California

Abstract: Per capita consumption of avocado in the United States has nearly doubled between 2000 and 2010. The California avocado industry supplies almost 40% of U.S. demand and the remaining 60% is supplied by imports from Latin America and New Zealand. The Tea Shot Hole Borer (TSHB) is an ambrosia beetle from Asia that forms a symbiosis with a new, yet undescribed Fusarium sp. and is a serious problem for the Israeli avocado industry (3). The beetle also causes severe damage on the branches of tea (Camelia sinensis) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
79
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(88 citation statements)
references
References 0 publications
0
79
1
Order By: Relevance
“…These diseases have developed in forest ecosystems, urban landscapes and agricultural settings, under varied environments, and in geographically diverse locations (2,42,51,56,73,89,94,98,114,133,137,149,169). The most significant of these diseases have had huge and surprising impacts.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…These diseases have developed in forest ecosystems, urban landscapes and agricultural settings, under varied environments, and in geographically diverse locations (2,42,51,56,73,89,94,98,114,133,137,149,169). The most significant of these diseases have had huge and surprising impacts.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, a branch dieback and canker disease was associated with E. fornicatus on avocado and other trees (32,42,114) (Fig. 11).…”
Section: Within the Last Decade E Fornicatus Has Invaded Many New Armentioning
confidence: 99%
See 2 more Smart Citations
“…This fungus and its associated ambrosia beetle vectors have been described as causing a serious dieback disease in Israel (Mendel et al 2012;Mendel et al 2017) and California (Eskalen et al 2012). Further examination has shown that molecular phylogenetics distinguishes six morphologically identical clades of F. euwallaceae, of which at least four attack and reproduce in avocado (O'Donnell et al 2016).…”
Section: Fusarium Diebackmentioning
confidence: 99%